Knowledge, awareness and attitudes among a group of Turkish dental students regarding molar incisor hypomineralization: a cross-sectional study - Özbey İpek Hilal; Bolaca Arif (BMC Oral Health)
Abstract Background Molar incisor hypomineralization (MIH) is estimated to affect more than 800 million people worldwide. The clinical management of MIH can be challenging. For dentists, to provide effective and high-quality dental care to people affected by MIH, it is essential that they improve their awareness, ability to describe the clinical situation, and knowledge of treatment modalities. Previous surveys conducted with students showed that only a limited number are confident in diagnosing MIH. The aim of the study was to assess the clinical knowledge and perceptions of 4th- and 5th-year dental students regarding the distribution, severity, etiology and treatment modalities of MIH. Methods In this cross-sectional study, a total of 194 students studying in the 4th- (85 students) and 5th- (109 students) years participated in the survey. The survey had 23 questions and two sections, the first of which was intended to gather demographic information about the students. The second part consisted of questions about the diagnosis, etiology, and treatment of MIH. The independent t test and the chi-square test was used to compare qualitative data. Results The majority of students (78.87%) stated that they had known about MIH. 5th-year students had known about MIH at a statistically significantly higher rate compared to 4th-year students (p = 0.0001). While only 19.69% of the participants stated that they could diagnose a patient with MIH, the proportion of 5th-year students who could make such a diagnosis was statistically significantly higher (p = 0.0001). The majority of the participants (96.39%) stated that they wanted MIH-related practices to be included more in their clinical education. The most desired topic to be included was diagnosis (91.98%). Conclusions The current study showed that students have some knowledge about MIH, but this knowledge is not sufficient, especially in terms of diagnosis and treatment. The students clearly wanted to develop their knowledge of MIH both theoretically and practically.